Mitochondrial iron-sulfur cluster dysfunction in neurodegenerative disease - Isaya, Grazia (Frontiers in Pharmacology, 2014)
Growing evidence supports a role for mitochondrial iron metabolism in the pathophysiology of neurodegenerative disorders such as Friedreich ataxia and Parkinson disease as well as in the motor and cognitive decline associated with the aging process. Iron-sulfur enzyme deficits and regional iron accumulation have been observed in each of these conditions. In spite of significant etiological, clinical and pathological differences that exist between Friedreich ataxia and Parkinson disease, it is possible that defects in mitochondrial iron-sulfur clusters biogenesis represent a common underlying mechanism leading to abnormal intracellular iron distribution with mitochondrial iron accumulation, OXPHOS deficits and oxidative stress in susceptible cells and specific regions of the nervous system. Moreover, a similar mechanism may contribute to the age-dependent iron accumulation that occurs in certain brain regions such as the globus pallidus and the substantia nigra. Targeting chelatable iron and reactive oxygen species appear as possible therapeutic options for Friedreich ataxia and Parkinson disease, and possibly other age-related neurodegenerative conditions. However, new technology to interrogate iron-sulfur cluster synthesis in humans is needed to (i) assess how defects in this pathway contribute to the natural history of neurodegenerative disorders and (ii) develop treatments to correct those defects early in the disease process, before they cause irreversible neuronal cell damage.